Identification and Analysis of the Design Process of Character Education for Students in Islamic Boarding Schools in West Sumatra - Hari, Wino Mulya; Indria, Anita; Hafizh, Muhammad (STIT Ahlussunnah Bukittinggi, 2023)
At the Miftahul Ulumi Syar’iyah Canduang Islamic boarding school, the vision and mission are seamlessly woven into the educational fabric, embracing diverse dimensions of character development outlined by religious and governmental directives. Through a collective effort, school administrators and teachers utilize these foundational principles to foster students' character growth, extending into extracurricular activities both within and outside the school premises. Researchers seek to investigate and evaluate the character education model implemented at the Miftahul Ulumi Syar’iyah Canduang Islamic boarding school, employing a descriptive methodology that encompasses field research techniques. Teachers oversee student activities throughout lessons and extracurriculars, ensuring active participation and guidance. The educational approach divides into intracurricular and extracurricular realms, with teachers directing classroom engagement and extracurricular pursuits occurring outside regular hours. Teacher evaluations, conducted weekly or monthly, monitor progress. The head of curriculum notes improved discipline and manners among students, reflecting positive character education outcomes.